COMMUNITY COEXISTENCE AND ATTITUDES TOWARD SUMATRAN ELEPHANT CONFLICT IN ARAS NAPAL KIRI, BESITANG, LANGKAT: A REVIEW OF HUMAN-ELEPHANT INTERACTION IN THE CONTEXT OF CONSERVATION - Alfi Syahrin Siregar; Ma'rifatin Zahra; Raden Garsetiasih (RADJA PUBLIKA, 2026)
The Sumatran elephant (Elephas maximus sumatranus) is a critically endangered species whose survival is increasingly threatened by human-elephant conflict (HEC) resulting from habitat fragmentation and expanding agricultural activities. This study investigates community coexistence and attitudes toward HEC in Dusun Aras Napal Kiri, Besitang, Langkat—a buffer zone adjacent to Gunung Leuser National Park (TNGL). A mixed-method approach combining quantitative surveys (n=28 households) and qualitative interviews was employed, supported by stakeholder analysis using an interest-influence matrix. Results show that 85% of respondents reported frequent conflicts, with 86% experiencing crop damage and annual economic losses equivalent to 1–1.5 months of household income. Despite the high conflict intensity, respondents exhibited a positive perception score of 1,191 out of 1,680, indicating ambivalent yet conservation-supportive attitudes—a condition defined as fragile coexistence. Stakeholder analysis identified UPT TNGL and UPT BKSDA as key players, community leaders and NGOs as agents to keep satisfied, while plantation companies and the general community occupy a monitoring role. The study recommends an integrated socio-ecological strategy encompassing community-based mitigation, adaptive agriculture, economic risk redistribution, and collaborative governance to transition toward sustainable coexistence.